LINING MATERIALS FOR CANALS: WATERPROOFING AND STRENGTH ANALYSIS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article provides a comprehensive scientific analysis of canal lining materials, with a focus on their waterproofing effectiveness and structural strength under various operational and environmental conditions. Drawing upon the latest advances in materials science, hydraulic engineering, and field experience from arid and semi-arid regions—including Central Asia and Uzbekistan—the review explores the evolution of canal lining technologies, from traditional clay and concrete to advanced geomembranes, composites, and polymer-modified concretes. The mechanisms of water loss, seepage control, chemical and mechanical durability, crack resistance, and long-term maintenance are critically assessed. Through the integration of laboratory testing, case studies, and performance modeling, the article evaluates the interplay between material selection, soil-canal interaction, environmental loads, and operational requirements. Emphasis is placed on the development and application of quantitative methods for waterproofing and strength assessment, including hydraulic conductivity measurement, finite element modeling, non-destructive testing, and lifecycle cost analysis. The article concludes with recommendations for best practices in material selection, design adaptation, quality assurance, and maintenance to ensure durable, efficient, and sustainable canal infrastructure in Uzbekistan and similar contexts.